Availability of Recently Described Ptychadena (Anura: Ptychadenidae) Nomina from Ethiopia - Colston, Timothy J.; Noonan, Brice P.; Smith, Megan L.; Pyron, R. Alexander (Zootaxa, 2020)
Frogs of the genus Ptychadena (Boulenger, 1917) have long been identified as harboring cryptic diversity and comprising numerous species-complexes (Largen 1997; Zimkus et al. 2017), and many authors have recognized the particularly high hidden richness in the Ethiopian highlands (Largen 1997; see Largen & Spawls 2010 and refs. within). This cryptic diversity was confirmed by recent molecular studies (Freilich et al. 2014; Smith et al. 2017a, Reyes-Velasco et al. 2018). Those authors identified a congruent set of evolutionarily distinct candidate species using both mitochondrial and nuclear DNA, and described the geographic and ecological isolation of these species in detail (Freilich et al. 2014; Smith et al. 2017a).